TRADE OPENNESS AND LONG-TERM ECONOMIC GROWTH: EMPIRICAL EVIDENCE FROM UZBEKISTAN AND KAZAKHSTAN - Agzamov Boburxon Boistxonovich, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract.  This  article  examines  how  trade  openness  relates  to  long-term economic growth in Uzbekistan and Kazakhstan, two landlocked economies that have pursued outward-oriented reforms in different sequences and at different speeds. Trade openness is commonly measured as the sum of exports and imports relative to GDP and  is  often  viewed  as  a  channel  for  productivity  gains  through  competition, technology diffusion, and access to larger markets. Yet, openness can also transmit external  shocks,  deepen  import  dependence,  and  amplify  commodity  cycles—especially  when  institutions,  logistics,  and  industrial  upgrading  lag  behind.  Using recent cross-country indicators and two country-focused empirical studies, the paper synthesizes  the  evidence  on  whether  openness  has  supported  growth  in  these economies and why results may differ across time horizons.